The promoter and multiple enhancers of the pou4f3 gene regulate expression in inner ear hair cells - Masuda, Masatsugu (Mol Neurobiol, 2016)
Few enhancers that target gene expression to inner ear hair cells (HCs) have been identified. Using transgenic analysis of eGFP reporter constructs and bioinformatics, we evaluated the control of pou4f3 gene expression, since it is expressed only in HCs within the inner ear, and continues to be expressed throughout life. An 8.5 kb genomic DNA fragment 5’ to the start codon, containing three regions of high cross-species homology drove expression in all embryonic and neonatal HCs, and adult vestibular and inner HCs, but not adult outer HCs. Transgenes with 0.4, 0.8, 2.5 or 6.5 kb of 5’ DNA did not produce HC expression. However, addition of the region from 6.5 to 7.2 kb produced expression in vestibular HCs and neonatal basal turn outer HCs, which also implicated the region from 7.2 kb to 8.5 kb in inner and apical outer HC expression. Deletion of the region from 0.4 to 5.5 kb 5’ from the 8.5 kb construct did not affect HC expression, further indicating lack of HC regulatory elements. When the region from 1 to 0.4 kb was replaced with the minimal promoter of the Ela1 gene, HC expression was maintained, but at a drastically reduced level. Bioinformatics identified regions of highly conserved sequence outside of the 8.5 kb, which contained POU4F3, GFI1, and LHX3 binding sites. These regions may be involved in maintaining POU4F3 expression in adult outer HCs. Our results identify separate enhancers at various locations that direct expression to different HC types at different ages, and determine that 0.4 kb of upstream sequence determines expression level. These data will assist in the identification of mutations in noncoding, regulatory regions of this deafness gene.